Enhancing the Quality of Life for Female Workers Through Transformational Leadership and Employee Empowerment Among Women Working in Financial Institutions in Bandung - Nenny Rinawati; Adhie Fasha Nurhadian; Windi Matsuko Danasasmita; Freity Cindy; Tasya Oktaviani (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2025)
This study aims to examine the relationship between leadership and employee empowerment, particularly for female workers in financial institutions, which is designated by the government to address the challenges of gender inequality. By understanding the role of leaders who create a supportive culture, where female workers feel valued and motivated to contribute maximally, this situation impacts the improvement of quality of life and organizational growth (in microfinance institutions). The indicators used to measure variable X is Transformational Leadership, variable Y is Employee Empowerment, while variable Z is Quality of Life.  The research method used in this study is quantitative method, with data collection techniques employing questionnaires. Then the data are processed by using PLS-SEM. 266 respondents were sampled for the study, which was tested by using Structural Equation Modeling (SEM). This analysis is used to determine whether there is a relationship between transformational leadership and quality of life through employee empowerment.  The results of the PLS-SEM analysis indicate that the coefficient calculation of Employee Empowerment on Quality of Life is significant, with a value of 0.296. Transformational Leadership on Employee Empowerment is also significant, with a value of 0.680. Transformational Leadership on Quality of Life is significant as well, with a value of 0.418. The model prediction criteria testing shows an R-square value of 0.462 and 0.431, indicating a reasonably good model. The f-square and Q²predict values also show positive values, along with the results of the PLS model prediction.